Health care for people living with HIV/AIDS accompanied by Centro de Testagem e Aconselhamento (Research, Society and Development, 2020)
Introduction: Socio-political transformations require a reappraisal of the demands of people living with Human Inmunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) (PLHA). Objective: To know the reality of health care provided to PLHA. Methods: qualitative-quantitative research, applied in PLHA accompanied at the Centro de Orientação e Apoio Sorológico/ Centro de Testagem e Aconselhamento (COAS/CTA) de Parnaíba-PI. Participants were 51 subjects, randomly selected, over 18 years old, registered for more than 6 months in the service; submitted to semi-structured questionnaires and interviews, with content submitted to discourse analysis, and to software SPSS, version 21, and Iramuteq. Result: the subjects preferentially use the health service of COAS, without other established itineraries; 96% state satisfaction, but they report difficulties regarding completeness and centralization. They recognize the importance of pharmacotherapy and complain of disrespect and social exclusion. Conclusions: PLHA develop marginal behavior in the health system; despite satisfaction, related to pharmacotherapy, face restrictions of access and completeness; and are victims of prejudice and stigmatization.